Study on Formant-Modulation Technique of Speech Intelligibility Assessment - Prodeus, Arkadiy (Innovations in Science and Technology Vol. 1, 2021)
The object of this paper was to study the statistical properties of the formant-modulation method for assessing speech intelligibility. Detailed description of the proposed formant-modulation method is presented. Analytical expressions for expectation and variance of estimators of a modulation coefficient and effective signal-to-noise ratio are obtained. Two situations which are most interesting in engineering applications are considered: a predominant noise disturbance and a predominant reverberant disturbance. Convenience in engineering applications equations, which permit finding efficient test signal duration for required measurement exactness, has been obtained. Computer modelling and experimental testing have confirmed efficiency of the formant-modulation method. The obtained results of comparing the formant and formant-modulation methods of assessing speech intelligibility made it possible to conclude that formant method is preferable for case of prevailing influence of noise. Relative error of formant method is about 0.15-0.20 of the formant-modulation method error and formant method estimation time is about 1/14 of formant-modulation method estimation time. However, the formant method cannot compete with the formant-modulation method with a significant effect of reverberation on speech intelligibility.